Controlled Drainage Option for Rice Water Management in Tidal Lowland Reclamation Areas of South Sumatra, Indonesia (Journal of Wetlands Environmental Management, 2024)
The problem of rice cultivation at C type tidal lowland (it does not receive high tidal water inundation) is water shortage. The research objective was to develop an open water level control model to support rainwater storage in order to provide the water requirement for rice crops. The research method was a field experiment. Land with an area of 16 ha (one tertiary block) was planted with rice variety Inpari 32 at first planting season (MT 1) for the period October-February 2019/2020. Rainwater harvesting was done by maintaining the open water level in the canal at minimum depth of 50 cm (controlled drainage) resulting in saturated soil conditions and enable rainwater storage, which can be used to fulfil the rice water requirement. The water control gate operation was done by applying a controlled drainage system (opened gate). Annual rainfall of > 2500 mm at normal conditions is sufficient for rice cultivation, but if the annual rainfall is less than 2500 mm such as in 2019, then water supply is needed by using pump irrigation at the initial planting period and generative phase period. A water pump is operated if there is no rainfall during more than 10 days. Rice production is very good with average yield of 7.5 ton/ha such as at first planting in 2020.